Estimating nutrient composition and polyphenol concentration using Near-Infrared Spectroscopy (NIRS) in tropical forages - HIKMAH A. PARASTIWI; NENG SRI H. LESTARI; YULIANRI R. YANZA; VINCENT NIDERKORN; RONI RIDWAN; ANURAGA JAYANEGARA (Society for Indonesian Biodiversity, 2023)
Abstract. Parastiwi HA, Lestari NSH, Yanza YR, Niderkorn V, Ridwan R, Jayanegara A. 2023. Estimating nutrient composition and polyphenol concentration using Near-Infrared Spectroscopy (NIRS) in tropical forages. Biodiversitas 24: 6652-6660. This study aimed to evaluate the accuracy and precision of Near-Infrared spectroscopy (NIRS) in determining nutrient composition and total phenol concentration in tropical forages. A total of 48 tropical forages from 33 species were subjected to measurements using conventional methods and NIRS equipment for rapid determination. The measured variables included Dry Matter (DM), ash, Crude Protein (CP), Ether Extract (EE), Crude Fiber (CF), and Total Phenolic (TP). The values obtained from NIRS were then statistically evaluated to obtain their coefficient of determination (R2), Standard Error (SE), and Root Mean Square Error (RMSE). Each tropical forage was assessed with three scanning repetitions, where two were conducted to calibrate NIRS determination, and another was performed to validate the NIRS results. All values obtained from the measured samples using both methods in this study were statistically analyzed through Partial Least Square (PLS) regression model. The results showed that the accuracy of NIRS for estimating nutrient content and total phenolic among different tropical forages was varied. NIRS was precise and accurate for estimating crude protein and total phenolic contents of tropical forages but showed lower accuracy for estimating EE content.